PENGARUH INSENTIF FINANSIAL, INSENTIF NON FINANSIAL DAN PENGALAMAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. BALI BARAMUNDI, BENOA - I Gusti Ayu Windasari; Anak Agung Ketut Sri Asih (Universitas Triatma Mulya, 2020)
The purpose of this research is : 1) know the influence of financial incentives on employee performance, 2) know the influence of non-financial incentives on employee performance, 3) know the impact of job experience on employee performance, 4) know the free variables that influence the dominant impact on employee performance, and 5) Know the great influence of financial incentives , non-financial incentives and work experience on the employee performance of PT Bali Baramundi, Benoa. The population of this research is all employees of PT. Bali Baramundi, Benoa which amounted to 60 people. The analysis tools used are multiple linear regression analyses. The hypothesis test used is T-Test to test the partial influence of financial incentives, non-financial incentives and job experience on employee performance, as well as analysis of determinations to analyse the magnitude of the effect of free variables on bonded variables. Acquired regression equation: Y = 0.745 + 0, 390X1 + 0, 233X2 + 0, 270X3. This Model shows that: 1) there is a positive and significant influence on the financial incentives to employee performance, 2) there are positive and significant influence of non-financial incentives to employee performance, 3) there are positive and significant influence of job experience on employee's performance, 4) Financial incentives are a free variable that has a dominant effect on employee performance, and 5) The magnitude of influence donated by financial incentives, non-financial incentives and job experience on the employee's performance of PT. Bali Baramundi, Benoa is 61.1%.